Israel : the first decade of independence - Troen, S. Ilan (Selwyn Ilan), 1940-; Lucas, Noah (SUNY series in Israeli studies., 1995)
Thirty-two authoritative essays expose the first decade of Israel's statehood to new analysis by historians and social scientists. Readers will develop a sharper understanding of change and continuity in society. The essays focus on 'social and economic transitions', 'literature and popular images', 'Israel and the diaspora', etc. This is a good choice for the leader/teacher of Israel courses of an academic nature.